Isolation and identification of Newcastle disease viruses from field outbreaks in chickens and pigeons (Bangladesh Veterinarian, 2013)
Eleven dead or sick birds submitted from farms in the year 2010 with a history of sudden death with respiratory and/or diarrhoeal signs were used for isolation and identification of Newcastle disease virus (NDV). All samples were subjected to routine necropsy. Pooled respiratory tissues were inoculated in embryonated chicken eggs and chicken embryo fibroblast (CEF) cell culture. The growth of NDV was confirmed by embryo mortality, cytopathic effects (CPE) in cell culture, haemagglutination (HA) and haemagglutination inhibition (HI) test. The presence of NDV was confirmed by reverse transcriptionpolymerase chain reaction (RT-PCR). At necropsy seven cases were tentatively diagnosed as Newcastle disease (ND). Out of seven ND-suspected samples, four yielded virus in both embryos and cell culture, while one was positive only in embryos, one only in cell culture and one sample was negative in both embryos and cell culture. RT-PCR successfully amplified a 766 bp fragment covering parts of Matrix and Fusion protein genes of NDV from the samples that were positive either in embryos or in cell culture. It is suggested that RT-PCR could be a rapid and sensitive tool for the detection of NDV. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14341 Bangl. vet. 2012. Vol. 29, No. 2, 41-48